Escala clima para criatividade em sala de aula: evidência de validade fatorial no contexto português - Morais, Maria de Fátima (2019)
Creative abilities are a requirement for the present and can be intentionally promoted from the beginning of the life course. The school environment appears as privileged in this promotion, being the facilitation of a creative climate in the classroom one of the ways to operationalize it. This climate can be investigated from the perspective of the students. The purpose of this study was to adapt, for the Portuguese context, the Classroom Climate for Creativity Scale, designed in Brazil. Five hundred and eighty-two students from 3rd and 4th grade participated in the study. The results indicate an instrument with 22 items, to be answered on a 5-point Likert scale, which evaluates four factors (Teacher Support for Expression of Student Ideas, Student Self-perception of Creativity, Student Interest in Learning, Student Autonomy). The psychometric characteristics of the instrument, in terms of accuracy and validity, were adequate. It may be useful in investigations on the perception of Portuguese students about creative teaching practices and on the self-evaluation of creativity, as well as for diagnosing the climate for creativity in the classroom